Hukum Kausalitas Sebagai Dasar Onto-epistemologis Mukjzat Pespektif Allamah Ṭabāṭabā’ī - Yaumil Wafa Aulia; Husen Alqaf (Pascasarjana IAIN Metro, 2023)
Miracles are events of extraordinary (khāriq al-‘ādat) in which its existence is believed and accepted. However, some theologians such as Asy‘ariyah do not accept the law of causality in miracles. For them God is the only cause and proximate cause for all events that occur in nature so that the natural order is nothing more than a habit of God (‘ādatullah), meaning that nature does not have definite laws. Thus, the only cause and the proximate cause of the occurrence of miracles is God, while the prophet only acts as a deterministic executor. This has implications for the absence of a prophetic doctrine, because the prophetic claims of the prophets as humans who were sent by God to convey revelations to humans cannot be accepted without miracles and even have implications for the perception of prophets as madmen. This research seeks to explain that miracles do not contradict the law of causality through an onto-epistemological basis. The ontological basis, explains how the law of causality occurs in miracles, how the immaterial world that is above becomes the cause and influences the realms below it, namely the material world, and what is the reality of the miracle. Then the soul and its actualization as its epistemological basis, namely how the soul of a prophet can do it. The two become an inseparable unit. This research method is descriptive-analytic-holistic using a philosophical approach from the perspective of Allamah Ṭabāṭabā’ī.